Lasers in Dentistry XX 2014
DOI: 10.1117/12.2040823
|View full text |Cite
|
Sign up to set email alerts
|

Change in clinical indices following laser or scalpel treatment for periodontitis: A split-mouth, randomized, multi-center trial

Abstract: Data are presented from a multi-center, prospective, longitudinal, clinical trial comparing four different treatments for periodontitis, (1) the LANAP™ protocol utilizing a FR pulsed-Nd:YAG laser; (2) flap surgery using the Modified Widman technique (MWF); (3) traditional scaling and root planing (SRP); and (4) coronal debridement (CD). Each treatment was randomized to a different quadrant. Fifty-one (54) subjects were recruited at five centers that included both private practice and university-based investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“… The only published randomized controlled trial involving LANAP ® compared the laser therapy with modified Widman flap surgery, scaling and root planing alone and supragingival scaling, and reported that the laser surgery was equal to the modified Widman flap surgery procedure with respect to reductions in probing depth and bleeding on probing. The results also showed the laser therapy to be only 0.2 mm better than scaling and root planing alone for probing depth reduction (Table ). Although LANAP ® is marketed as a protocol that promotes bone regeneration in periodontitis defects, there was no mention of bone regeneration in the published results. The average difference in probing depth reduction for LANAP ® ‐treated sites vs. scaling and root planing only, for the five studies presenting such data (Table ), was 0.56 mm for pockets of 3–6 mm and 0.24 mm for pockets of > 6 mm (Table ).…”
Section: Summary Of the Lanap® Protocol And Treatment Of Periodontitismentioning
confidence: 98%
See 4 more Smart Citations
“… The only published randomized controlled trial involving LANAP ® compared the laser therapy with modified Widman flap surgery, scaling and root planing alone and supragingival scaling, and reported that the laser surgery was equal to the modified Widman flap surgery procedure with respect to reductions in probing depth and bleeding on probing. The results also showed the laser therapy to be only 0.2 mm better than scaling and root planing alone for probing depth reduction (Table ). Although LANAP ® is marketed as a protocol that promotes bone regeneration in periodontitis defects, there was no mention of bone regeneration in the published results. The average difference in probing depth reduction for LANAP ® ‐treated sites vs. scaling and root planing only, for the five studies presenting such data (Table ), was 0.56 mm for pockets of 3–6 mm and 0.24 mm for pockets of > 6 mm (Table ).…”
Section: Summary Of the Lanap® Protocol And Treatment Of Periodontitismentioning
confidence: 98%
“…Furthermore, it should be noted that two other studies did not report on tooth/site selection and may have involved only single‐rooted teeth. Lastly, the one major randomized controlled trial did not report gains or loss in clinical attachment level. Given these flaws in experimental design, a judgement of clinical significance becomes an exercise in futility. Only one of six published studies in the LANAP ® series presented data concerning reductions in bleeding on probing .…”
Section: Summary Of the Lanap® Protocol And Treatment Of Periodontitismentioning
confidence: 99%
See 3 more Smart Citations